Forces Applied during Transvenous Implantable Cardioverter Defibrillator Lead Removal - Lennerz, Carsten (Hindawi Publishing Corporation, 2014)
Methods. 17 physicians, experienced in transvenous lead removal, performed a lead extraction manoeuvre of an ICD lead on a torso phantom. They were advised to stop traction only when further traction would be considered as harmful to the patient or when—based on their experience—a change in the extraction strategy was indicated. Traction forces were recorded with a digital precision gauge. Results. Median traction forces on the endocardium were 10.9 N (range from 3.0 N to 24.7 N and interquartile range from 7.9 to 15.3). Forces applied to the proximal end were estimated to be 10% higher than those measured at the tip of the lead due to a friction loss. Conclusion. A traction force of around 11 N is typically exerted during standard transvenous extraction of ICD leads. A traction threshold for a safe procedure derived from a pool of experienced extractionists may be helpful for the development of required adequate simulator trainings.